2012 Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2012
DOI: 10.1109/embc.2012.6346923
|View full text |Cite
|
Sign up to set email alerts
|

Reducing classification accuracy degradation of pattern recognition based myoelectric control caused by electrode shift using a high density electrode array

Abstract: The robustness and usability of pattern recognition based myoelectric control systems degrade significantly if the sensors are displaced during usage. This effect inevitably occurs during donning, doffing or using an upper-limb prosthesis over a longer period of time. Electrode shift has been previously studied but remains an unsolved problem. In this study we investigate if increasing the number of electrode channels and recording locations can improve the degraded classification accuracy caused by electrode … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…The multi-channel sEMG recording provides useful information to improve the recognition of fine movements. On the other hand it requires a complex and cumbersome setup with the need to place many electrodes on the forearm and to manage many connectors [10] [29] . In order to simplify the electrode setup Farina et al used a textile sleeve with four grids of 5×5 electrodes to detect sEMG signals from upper arm and forearm for the recognition of wrist and forearm movements [30] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The multi-channel sEMG recording provides useful information to improve the recognition of fine movements. On the other hand it requires a complex and cumbersome setup with the need to place many electrodes on the forearm and to manage many connectors [10] [29] . In order to simplify the electrode setup Farina et al used a textile sleeve with four grids of 5×5 electrodes to detect sEMG signals from upper arm and forearm for the recognition of wrist and forearm movements [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Geng et al [41] showed that the impact of arm position on sEMG pattern-recognition performances is a little stronger in intact arm than in amputated arm. Boschmann and Platzner [29] showed that, to compensate an electrode displacement of 1 cm on the classification accuracy, the number of detection points must be increased from 8 to 32. Hargrove et al [42] studied the effect of 1 cm electrode displacement in longitudinal and/or transversal direction on pattern classification accuracy using an IED of 3 cm, and proposed a classifier training strategy to accommodate performance degradation.…”
Section: Discussionmentioning
confidence: 99%
“…To ameliorate the effects of inter-session variability, data augmentation schemes [12,13] and model adaptation techniques [2,14,15,16] were developed. However, the problem of recognizing a large set of gestures in a new recording session is still far from being solved, both in terms of the recognition accuracy and the complexity of the calibration process.…”
Section: Introductionmentioning
confidence: 99%
“…In order to simulate the effect of electrode shift in the experiments performed, multiple electrodes are placed in adjacent areas of the original locations of the electrodes (Hargrove et al, 2008 ; Boschmann and Platzner, 2012 ). The most common experimental procedure consists of training the classifiers on features extracted from the original signals and testing the classifier on features from the shifted signals.…”
Section: Causes Of Emg Variability With Timementioning
confidence: 99%
“…The most common experimental procedure consists of training the classifiers on features extracted from the original signals and testing the classifier on features from the shifted signals. The maximum electrode displacement distance that is likely to occur in the normal everyday use of the prosthetic hand is noted in different studies as 1 cm (Hargrove et al, 2008 ; Boschmann and Platzner, 2012 , 2014 ; Muceli et al, 2014 ; Pan et al, 2015 ; Stango et al, 2015 ).…”
Section: Causes Of Emg Variability With Timementioning
confidence: 99%